Proton spin-echo magnetometer: a novel approach for magnetic field measurement in residual field gradient. (15th May 2015) - Shim, Jeong Hyun; Lee, Seong-Joo; Hwang, Seong-min; Yu, Kwon Kyu; Kim, Kiwoong
Abstract: We demonstrate a proton spin echo magnetometer, in which the interrogation time is not limited by and can be prolonged to T 2 . Therefore, even under a severe field gradient, the precision of the measurement does not degrade. We devised a phase linearization method that enables accurate estimation of the precession frequency from a spin-echo train. With proton spins in deoxygenated tetramethylsilane and a superconducting quantum interference device-detected NMR system at KRISS, an average field of around 5 μT was measured with an uncertainty of 0.42 nT in the presence of a field gradient of 12.8 μT m −1 . This implies that our system tolerated a 25% variation in magnetic field over the sample area. The proton spin-echo magnetometer will be useful in measuring magnetic fields without compensating for residual field gradients.